Polyhexanide-containing solution reduces ciliary beat frequency of human nasal epithelial cells in vitro - Birk, Richard; Aderhold, Marc Christoph; Stern-Sträter, Jens; Hörmann, Karl; Sommer, Ulrich (European archives of oto-rhino-laryngology and head & neck, 2015)
In ENT, polyhexanide-containing solutions are used to treat nasal infections caused by multiresistant bacteria like methicillin-resistant Staphylococcus aureus. Many forms of commercial nasal solutions containing polyhexanide exist, such as gels or solutions for topical use. Data regarding the influence of polyhexanide on ciliary beat frequency (CBF) are lacking to date. We tested the CBF of nasal ciliated epithelial cells under the influence of a commercially available polyhexanide-containing solution (Lavasept® Concentrate) in a therapeutic concentration (0.04, 0.02 %). In addition, we tested the concentrations of 0.1 and 0.01 %. Cells were visualized with a phase contrast microscope, and the CBF was measured with the SAVA system’s region of interest method. Ringer’s solution and macrogol served as negative controls. A therapeutic concentration of Lavasept significantly reduced CBF in a time- and concentration-dependent manner. After 1 min, the CBF was reduced from 8.90 ± 1.64 to 5.00 ± 3.72 Hz with a concentration of 0.04 % (p value = 0.001). After 10 min, all cilia stopped beating. After 5 min, a 0.02 % solution of Lavasept concentrate decreased CBF significantly from 8.64 ± 1.71 to 3.30 ± 3.27 Hz (p value < 0.001). In conclusion, CBF of human nasal epithelia is significantly reduced with the use of the polyhexanide-containing solution Lavasept in some therapeutic concentrations. Due to our findings in this study, Lavasept should be used on ciliated mucosa only with caution and in a concentration of 0.02 %.